Colonic transit time and rectoanal videomanometry in Parkinson's disease. Issue 2 (1st February 2003) - Sakakibara, R; Odaka, T; Uchiyama, T; Asahina, M; Yamaguchi, K; Yamaguchi, T; Yamanishi, T; Hattori, T
Abstract : Background: Constipation is a prominent lower gastrointestinal tract dysfunction that occurs frequently in Parkinson's disease (PD). Objective: To investigate colonic transport and dynamic rectoanal behaviour during filling and defecation in patients with PD. Methods: Colonic transit time (CTT) and rectoanal videomanometry analyses were performed in 12 patients with PD (10 men and 2 women; mean age, 68 years, mean duration of disease, five years; mean Hoehn and Yahr grade, 3; decreased stool frequency (<3 times a week) in six, difficulty in stool expulsion in eight) and 10 age matched normal control subjects (7 men and 3 women; mean age, 62 years; decreased stool frequency in two, difficulty in stool expulsion in two). Results: In the PD patients, CTT was significantly prolonged in the rectosigmoid segment (p<0.05) and total colon (p<0.01) compared with the control subjects. At the resting state, anal closure and squeeze pressures of PD patients were lower than those in control subjects, though not statistically significant. However, the PD patients showed a smaller increase in abdominal pressure on coughing (p<0.01) and straining (p<0.01). The sphincter motor unit potentials of the patients were normal. During filling, PD patients showed normal rectal volumes at first sensation and maximum desire to defecate, and normal rectal compliance. However, they showed smaller amplitude in phasic rectal contraction (p<0.05), which was accompanied by an increase in anal pressure that normally decreased, together with leaking in two patients. During defecation, most PD patients could not defecate completely with larger post-defecation residuals (p<0.01). PD patients had weak abdominal strain and smaller rectal contraction on defecation than those in control subjects, though these differences were not statistically significant. However, the PD patients had larger anal contraction on defecation (p<0.05), evidence of paradoxical sphincter contraction on defecation (PSD). Conclusions: Slow colonic transit, decreased phasic rectal contraction, weak abdominal strain, and PSD were all features in our PD patients with frequent constipation.